The interface between historical geography and the holistic history of Ancient Israel - Scheffler, Eben 1953- (1996)
In this article it is argued that in the past (despite recognitions of the comprehensive nature of history) historical geography has too one-sidely been used to elucidate the political dimension of Ancient Israelite history. In a holistic approach to history four dimensions of history are distinguished as a matter of procedure, and it is indicated by means of examples that historical geography not merely relates to history or illustrates it, but is indispensable to the understanding of all four dimensions (politica-socio-cultural, religio-political, communicative) of history in their mutual and interrelated complexity.
Keywords: Ancient Israel history; Geographical features of Palestine; Historical geography; Holistic history; Importance of Jerusalem; Palestine's strategic position; Politica-socio-cultural aspect; Religio-political dimentions